Reflections on the Russia-Ukraine War (Leiden University Press, 2024)
The Russia-Ukraine war is a multifaceted beast. It ranges from fighting on the ground to high diplomacy, from domestic anti-war protests to international weapon supplies, from justification through sham referenda to coercion via economic sabotage, and from operational misdirection to covering up war crimes. There are close connections between these facets: the collapse of a front leads to the discovery of mass graves; the delivery of weapon systems depends on Zelensky’s appeal to the international community; sham referenda followed by annexation enable accusations of unwillingly mobilised soldiers who refuse to defend the motherland.